2015
DOI: 10.1002/ange.201507939
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphole Oxide Based Fluorescent Dye with Exceptional Resistance to Photobleaching: A Practical Tool for Continuous Imaging in STED Microscopy

Abstract: The development of stimulated emission depletion (STED) microscopyr epresented am ajor breakthrough in cellular and molecular biology.H owever,t he intense laser beams required for both excitation and STED usually provoke rapid photobleaching of fluorescent molecular probes,w hich significantly limits the performance and practical utility of STED microscopy. We herein developed ap hotoresistant fluorescent dye C-Naphoxa sapractical tool for STED imaging.Withexcitation using either a l = 405 or 488 nm laser in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 19 publications
(18 reference statements)
0
27
1
Order By: Relevance
“…contains an electron-withdrawing phosphine oxide (P = O) moiety. We have previously reported that the donor-π-acceptor-type dye C-Naphox, which consists of a naphthophosphole P-oxide skeleton and an electron-donating triphenylamine moiety, exhibits sufficient photoresistance to allow successive STED scans (11). While this dye showed significantly decreased fluorescence quantum yields (Φ F ) in aqueous media due to its intramolecular charge transfer (ICT) character in the excited state, intense fluorescence was revived in nonpolar environments.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…contains an electron-withdrawing phosphine oxide (P = O) moiety. We have previously reported that the donor-π-acceptor-type dye C-Naphox, which consists of a naphthophosphole P-oxide skeleton and an electron-donating triphenylamine moiety, exhibits sufficient photoresistance to allow successive STED scans (11). While this dye showed significantly decreased fluorescence quantum yields (Φ F ) in aqueous media due to its intramolecular charge transfer (ICT) character in the excited state, intense fluorescence was revived in nonpolar environments.…”
Section: Significancementioning
confidence: 99%
“…To solve this issue, we have recently proposed a structural reinforcement strategy of electron-deficient π-conjugated molecular skeletons, which significantly improves the photostability of fluorophores (11). Based on this strategy, superphotostable phospholebased fluorescent molecules have been developed, and these allow multiple acquisition of STED images under physiological conditions (12).…”
mentioning
confidence: 99%
“…The components of S TDM also suggest that CBF-S has lower anisotropy in its shape (low λ S and S LX~0 .23), which is the main reason for the low S TDM , similarly to the cases found on CP2 and CBM. Originally, the phenyl group attached to the phosphorus has been designed and required because of the synthetic reason, ie, availability of the starting materials and the stability toward the reaction conditions 39,47,48 . Here it is theoretically suggested that the structural nature, ie, >P(=O)Ph, also plays an important role in realising negative fluorescence anisotropy of phosphole oxide-based dyes in the present NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently the negative anisotropy of a phosphole oxide-based dye, C-Naphox 39 , in NLC was reported 40 . Since this dye has a high photobleaching resistance, the detailed FPOM study of NLC defects has become possible, eg, uncovering their three-dimensional structures being based on alignment information complementary to that given by the dyes with positive anisotropy.…”
mentioning
confidence: 99%
See 1 more Smart Citation